A study on contingency plan and mitigation plan and projection tool for the company Gildan Activewear Bangladesh for uninterrupted production - Parvez, Saimon (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.